Upaya Peningkatan Kinerja Karyawan Bagian Power Plant Berbasis Budaya Organisasi dan Lingkungan Kerja Fisik pada Perusahaan X di Purwakarta - Alfariz, Mochamad Rezi; Romi, Mochamad Vrans (Universitas Batanghari, 2024)
Competent and high-performing human resources ensure that the company runs well, from the data obtained there are several employees whose performance is still lacking. Factors that affect the good and bad performance of employees are organizational culture and physical work environment. This study aims to determine the relationship between organizational culture and physical work environment on the performance of power plant employees at company x in Purwakarta. The method in this study uses quantitative methods with sampling techniques, namely all populations sampled. Data collection techniques by distributing questionnaires and interviews. The data analysis technique uses descriptive methods and associative methods and data analysis, namely multiple regression analysis by interpreting the output table of the SPSS version 25 program. The results showed that organizational culture partially affects employee performance, and the physical work environment partially affects employee performance. Furthermore, organizational culture and physical work environment simultaneously affect the performance of power plant employees at company x in Purwakarta.